Peningkatan Keterampilan Berpikir Kreatif Siswa dengan Menerapkan Pembelajaran STEM di Sekolah Dasar - Erniza, Erniza; Witarsa, Ramdhan; Marta, Rusdial (Universitas Negeri Makassar, 2023)
Thinking skill is one of the skills that must be possessed by elementary school students. This research aims to improve students' creative thinking skills using science, technology, engineering, and mathematics learning models. The method used in this research is the classroom action research method. This method has four stages, namely planning, implementation, observation, and reflection. The research subjects were 27 students, consisting of 15 male students and 12 female students. Data collection techniques used are observation and documentation. The research instrument used was the teacher activity observation sheet and the student activity observation sheet. The results of this research indicate that there is an increase in students' creative thinking skills from pre-action to cycle 1 by 10.75%. The increase in students' creative thinking skills also occurred in cycle 1 to cycle 2 by 8.24%. The application of science, technology, engineering, and mathematics learning models can improve students' overall creative thinking skills by 18.99%. Therefore, this research can be used as a reference for teachers in implementing science learning to apply science, technology, engineering, and mathematics learning models so that students become more active in participating in learning and can facilitate the needs of elementary school students in improving their thinking skills.